Interlaboratory Comparison Investigations (ICIs) for human biomonitoring of chromium as part of the quality assurance programme under HBM4EU - Nübler, Stefanie; Schäfer, Moritz; Haji-Abbas-Zarrabi, Karin; Marković, Stefan; Marković, Katarina; Esteban López, Marta; Castaño, Argelia; Mol, Hans; Koch, Holger M; Antignac, Jean-Philippe; Hajslova, Jana; Thomsen, Cathrine; et al. (Journal of trace elements in medicine and biology, 2022)
BACKGROUND: The pan-European human biomonitoring initiative HBM4EU targets the harmonization of human biomonitoring (HBM) procedures and data for both environmental and occupational exposure, including chromium. The determination of chromium in urine (U-Cr), plasma (P-Cr) and whole blood (WB-Cr) is a common HBM application in employees occupationally exposed to chromium (VI) compounds. METHODS: European laboratories which have registered as candidate laboratories for chromium analysis within HBM4EU were invited to participate in a quality assurance/qualitycontrol (QA/QC) programme comprising interlaboratory comparison investigations (ICI) for the parameters U-Cr, P-Cr and WB-Cr. Participating laboratories received two samples of different concentrations in each of four rounds and were asked to analyse the samples using their standard analytical procedure. The data were evaluated by the Z-score approach and were reported to the participants after each round. RESULTS: The majority of the 29 participating laboratories obtained satisfactory results, although low limits of quantification were required to quantify chromium concentrations in some of the ICI materials. The robust relative standard deviation of the participants' results (study RSDR) obtained from all ICI runs ranged from 6 to 16 % for U-Cr, 7-18 % for P-Cr and 4-47 % for WB-Cr. The application of both inductively coupled plasma mass spectrometry (ICP-MS) and electrothermal atomic absorption spectrometry (EAAS) appeared appropriate for the determination of chromium in urine, plasma and whole blood with regard to occupational exposure levels. CONCLUSION: This QA/QC programme succeeded in establishing a network of laboratories with high analytical comparability and accuracy for the analysis of chromium across Europe.
Keywords: Biological Monitoring; Spectrophotometry, Atomic; Chromium; Occupational exposure; monitorování životního prostředí; lidé; Occupational Exposure; HBM4EU; Whole blood; Human biomonitoring (HBM); spektrofotometrie atomová; Humans; Electrothermal atomic absorption spectrometry (EAAS); chrom; Plasma; pracovní expozice; Red blood cells; Inductively coupled plasma mass spectrometry (ICP-MS); biologický monitoring; Environmental Monitoring; Urine; Interlaboratory comparison investigation (ICI)